Evaluation of the visibility of colored objects under led lighting with various correlated color temperatures. Issue 1 (4th April 2016) - Hong, Seongkwan; Kim, Intae; Kim, Hyunsun; Sohn, Arom; Choi, An‐Seop; Sung, Minki; Jeong, Jae‐Weon
Abstract: This study proposes a "visibility" concept of colored objects that includes a combination of color brightness and appearance perception of colored objects that are illuminated by seven LED lights (each with a CIE color rendering index under 80 but with various correlated color temperatures). To determine the brightness perception of colored objects, luminance calculations and measurements were conducted. The areas of the "color brightness graph" in this study correspond to the results of eight different color sample papers under each of the LED lights with different CCTs. The luminance values were calculated by multiplying the SPD by the spectral luminous efficiency and spectral reflectance of a colored object. The luminance values were measured under these conditions to identify the relationship between the luminance calculations and the measured values. Efficient CCTs were identified for each color sample in terms of the brightness of the colored object. Further subjective evaluations were also conducted to identify the relationship between luminance values and subjective brightness perception. In addition, subjective evaluations of the color appearance perception were conducted to identify the overall visibility concept of colored objects. The subjective evaluations included brightness perception, color appearance, and similarity of the reference light source. The visibility of the colored objects was analyzed according to the results of the brightness and appearance perception of the colored objects that were illuminated by LED lights with various CCTs. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 78–88, 2017